RELEVANSI MAQĀṢID AL-SYARĪ’AH DALAM KONTEKS HUKUM ISLAM KONTEMPORER: SEBUAH KAJIAN TEORITIS DAN APLIKATIF - S, Samsidar; Supardin, Supardin; Dalle, Jumarni; Ishak, Nurfaika; Suhartati, Suhartati (IAIN BONE, 2025)
The objective of this study is to explore and analyze the application of maqÄá¹£id al-syarÄ«'ah in the context of contemporary Islamic law, with a focus on how maqÄá¹£id principles can be applied to address the challenges faced by Islamic law today. In an era of globalization and rapid social change, many aspects of Islamic law need to be adapted in order to remain relevant and responsive to the needs of modern society.. The aim of this research is to explore and analyze the application of maqÄá¹£id al-syarÄ«'ah in formulating fairer and more relevant laws, as well as to provide applicable examples of how these principles can be used in real cases, such as family law and sharia economics. Using a kualitatif approach, this study analyzes relevant literature and legal documents. The results indicate that the application of maqÄá¹£id al-syarÄ«'ah can not only improve adherence to Islamic law but also provide innovative solutions for complex contemporary problems. It is hoped that this research can make a significant contribution to the development of Islamic law that is more responsive and inclusive, as well as strengthening understanding of maqÄá¹£id al-syarÄ«'ah in a modern context.